Design and Motion Simulation of a Soft Robot for Crawling in Pipes - Zhang Yu; Huang Peiyu; You Bo; Yu Zhibin; Li Dongjie; Dong Guoqi (Applied Bionics and Biomechanics)
In recent years, soft pipeline robot, as a new concept, is proposed to adapt to tunnel. The soft pipeline robots are made of soft materials such as rubber or silicone. These materials have good elasticity, which enhance the adaptability of the soft pipeline robot. Therefore, the soft pipeline robot has better performance on deformability than rigid robot. However, the structure of tunnel is complex and varied that brought challenges on design structure of soft pipeline robot. In this paper, we propose soft pipeline robot with simple structure and easy fabrication, which can be realized straight, turning motion in a variety of tunnels with different diameters. The soft pipeline robot composed of two types of structure, which are expansion part and deformation part. Front and rear deformation part for bending and position fixation, and middle expansion part for elongation, so the pipeline soft robot can be moved in various structures of tunnels. Moreover, the locomotion ability and adaptability in tunnel are verified by simulating on software. The structure of chamber proposed in this paper can guide the design method of soft pipeline robot.